Disruptive Game Online and Social Personality: Case Study at SDN Asem Kumbang Katingan Regency - Mazrur Mazrur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to describe the positive impact of playing games online on children's social personalities, as well as describing the negative impact of playing games online on social personalities at SDN Asem Kumbang, Katingan Regency. This research was compiled using a descriptive qualitative approach. The research subjects totaled seven children of SDN Asem Kumbang, Katingan Regency and the informants were three parents and two teachers. Data collection techniques using observation, interviews, and documentation. Validation of the data in this study using source simulation. The data analysis uses four stages, namely collecting, summarizing, presenting, and making conclusions. The results of this study indicate that the positive impact of playing games online for children at SDN Asem Kumbang, Katingan Regency, includes socializing, cooperation, and sympathy. While the negative impact is playing games online on the social personality of the children of SDN Asem Kumbang Katingan Regency are addicted, speaking rudely and dirty, disobedient, dispute or fight, and teasing or mocking.